Studying the link between physiological performance of Crotalaria ochroleuca and the distribution of Ca, P, K and S in seeds with X-ray fluorescence - Cotrim, Mayara Fávero; Da Silva, Josué Bispo; Dos Santos Lourenço, Flávia Mendes [UNESP]; Teixeira, Anielli Verzotto; Gava, Ricardo; Alves, Charline Zaratin; Da Silva Candido, Ana Carina; Campos, Cid Naudi Silva; Pereira, Márcio Dias; Torres, Salvador Barros; Bacchetta, Gianluigi; Teodoro, Paulo Eduardo (Public Library of Science (PLoS), 2019)
This study describes the use of X-ray fluorescence spectroscopy in Crotalaria ochroleuca seed technology. This work evaluated X-ray fluorescence techniques to estimate the physiological performance of different C. ochroleuca seed coat colours based on the concentration and distribution of Ca, P, K, and S in seed structures. The treatments consisted of seeds separated by coat colours (yellow, green, and red) and a control treatment (colour mix according to their natural occurrence in commercial lots), and was carried out in a completely randomized design, with four replications. The physiological performance was evaluated by analyzing the water content, germination, first germination count, germination speed index, electrical conductivity, seedling emergence, and seedling length and dry mass. X-ray fluorescence spectroscopy techniques were carried out with quantitative analyses (Ca, P, K, and S concentration in the seed coat and the whole seed) and qualitative analyses (macronutrient mapping). The EDXRF and μ-XRF techniques are efficient and promising to differentiate the physiological performance of C. ochroleuca seeds, based on the concentration and distribution of Ca, P, K, and S in different structures. Ca is predominant in the seed coat, and K, S, and P are found throughout the embryonic axis. Seeds of yellow and green coats have higher nutrients concentration and distribution in the embryonic axis, revealing high germinative capacity and physiological performance. Seeds of red coat have higher nutrients concentration in the seed coat and lower assimilation, showing less vigour, which interferes directly in the quality of commercial lots.